Potentials and Limitations of Implementing Linear Infiltration Systems on Urban Streets - Frank Sleegers (Fábos Conference on Landscape and Greenway Planning, 2013)
Increasing infiltration systems in urban environments has become a major focus of our discipline to reduce the harmful impact of stormwater on urban watersheds. Two recent studies were conducted by the author of this paper (Sleegers and Brabec; 2013, Sleegers, 2013) with the focus on evaluating the aesthetics of linear urban infiltration systems on urban streets. Each study revealed challenges and limitations of these systems on various levels. What are the crucial criteria to propagate infiltration along streets, raise their acceptance and make them more usable? The purpose of this paper is to investigate the challenges and limitations of urban infiltration systems and propose recommendations for further implementation.
Keywords: greenways; urban; infiltration; linear; system; green infrastructure; street; road